THE IMPACT OF DIGITAL INNOVATION ON E-COMMERCE YOUNG CUSTOMER SATISFACTION IN VIETNAM - Le, Minh-Hoa; Duong, Que-Nhu; Nguyen, Hieu-Nghia; Au, Quynh-Nhu; Pham, Nhat-Nam (Bank Indonesia, 2025)
This study looks at the influence of digital innovation, notably AI-driven chatbots, on e-commerce consumer satisfaction among young customers in Vietnam. It investigates key factors influencing user satisfaction employing frameworks such as the Uses and Gratifications Theory (U&G), Technology Acceptance Model (TAM), and the Unified Theory of Acceptance and Use of Technology (UTAUT), including utilitarian, hedonic, technological, and social gratifications, privacy risk, and social influence. This research applies a quantitative method, with data collected through an online survey utilising snowball sampling, yielding responses from 1,007 individuals aged 18 to 30. SPSS and PLS-SEM tools are used in the statistical analysis. This study finds that utilitarian, hedonic, technological, and social gratifications positively and substantially impact user satisfaction. Aside from this finding, when engaging with chatbots, consumers are often affected by suggestions and endorsements from peers and their larger social context. This highlights the significance of peer validation and social dynamics in determining user satisfaction. Additionally, Privacy Risks do not substantially impact satisfaction, indicating that customers prioritise practical and emotional advantages over data security concerns when engaging with chatbots. Practical implications include strategically using digital innovation, making reasonable assumptions about privacy risks, and adding social elements to improve consumer satisfaction in Vietnam’s thriving e-commerce industry. This study provides valuable insights for companies navigating digital innovation in Vietnam’s e-commerce ecosystem and digital banking.